Fault-tolerant capability of star connected symmetrical six-phase induction machine with single and two isolated neutrals / Wan Noraishah Wan Abdul Munim - Wan Noraishah , Wan Abdul Munim (2020)
Traditionally, electrical machines have been designed to operate with single- or three phase power supplies. In the early stage of power electronics development, three-phase machine suffers problems such as high torque ripple due to low order harmonics during six-step switching and limited current handling capacity of the power switches. This has motivated the use of multiphase machines which is capable of mitigating the aforementioned issues. The revival of multiphase machine research is mainly motivated by the need for more reliable drive systems. The vector space decomposition (VSD) model is used for a healthy multiphase machine as the basis for control to transform the phase variables to the decoupled stationary-frame variables, which consist of flux and torque producing α-β components and loss producing x-y and zero sequence components. For normal operation, the machine is controlled by regulating the α-β current components while keeping the x-y and zero sequence components to zero. The discussed control structure become invalid when the machine suffers from fault, such as when one of the phase connection is open-circuited. However, the multiphase machine is capable to This research presents a study of fault-tolerant of star-connected symmetrical six-phase induction machine (S6-IM) by evaluating the capability of S6-IM in terms of current and voltage limits. This thesis proposes the comparison between single (1N) and two isolated neutral points (2N) considering up to three simultaneous open-circuit faults. Indirect rotor field-oriented control (IRFOC) is used to generate the α, β, x, y, 0+ and 0- reference voltages. Vector control separately regulates the torque and flux producing components of the stator current and hence requires accurate current control which can be achieved using a linear current regulation. Meanwhile, reconfiguration of the controller is minimized when transiting from pre-fault to post-fault operation based on normal decoupling transformation without changing the machine parameter. Two modes of post fault operation namely minimum loss (ML) and maximum torque (MT) are further analyzed. The maximum torque is expected to be the same as the optimal amplitude. Moreover in post-fault operation, the voltage limit analysis plays an important element for post-fault control as the voltage limit has a direct impact on the speed limit. Hence, machine voltage equations require accurate knowledge of the machine parameters, especially for the rotor time constant in IRFOC. The machine equation in the α-β frame is used to perform machine parameter estimation. The accuracy of the estimated machine parameter is crucial to determine the maximum line-to-line voltages. Hence, a test rig capable of implementing and evaluating the fault-tolerant operation of an S6-IM is developed. The simulation and experimental results obtained confirm the validity and efficiency of the most suitable proposed method for the fault-tolerant capability of star connected S6-IM with single and two isolated neutrals.